Versatile coordination of a reactive P, N-ligand toward boron, aluminum and gallium and interconversion reactivity. Issue 27 (16th June 2016) - Devillard, M.; Alvarez Lamsfus, C.; Vreeken, V.; Maron, L.; van der Vlugt, J. I.
Abstract : The unique and well-defined coordination chemistry of a reactive lutidine-derived dearomatized phosphino-amido ligand toward Group 13 complexes is presented. Abstract : The synthesis and reactivity of the first Group 13 complexes bearing a dearomatized phosphino-amido ligandL are reported, i.e. alane AlEt2 (L )1, gallane GaCl2 (L )2 and borane B(Cl)(Ph)(L )3 . The three complexes react very differently with Group 13 trihalogenides, providing access to zwitterionic anti -3 ·GaCl 3 and the unique bis(metalloid)5 ·BCl 2, with the boron center part of a highly unusual anionic four-membered ring (charge on C) and Ga bound to P. The coordination chemistry and the various transformations are supported by DFT calculations, X-ray crystallography and multinuclear NMR spectroscopic data.